Click Variations on the Synthesis of 2-Nitrophenyl-4-aryl-1,2,3-triazoles without Isolation of 2-Nitrophenyl Azides - Roux, Amélie; Cisnetti, Federico (Synlett, 2020)
We report a series of efficient procedures to prepare 2-nitrophenyl-4-aryl-1,2,3-triazoles avoiding the isolation of potentially hazardous 2-nitrophenyl azides. An organocatalyzed azide-enolate variant allows efficient access to the target compounds while it was shown that a metal-catalyzed azide-alkyne procedure involving a preliminary Sonogashira coupling was feasible starting from electron-deficient aryl iodides.
Keywords: click chemistry; azides; alkynes; enolates; triazoles; organocatalysis